Thromboembolic Reaction Following Wall Puncture in Arterioles and Venules of the Rabbit Mesentery - oude Egbrink, Mirjam G A; Tangelder, Geert Jan; Slaaf, Dick W; Reneman, Robert S (Thrombosis and Haemostasis, 1988)
The walls of rabbit mesenteric arterioles and venules (diameter 20 to 40 pm) were punctured with glass micropipets (tip diameter 6 to 8 pm). Thromboembolic reactions resulting from this standardized, small mechanical vessel wall injury could be quantified in vivo with the use of intravital video-microscopy. Following induction of the injury thrombus growth started immediately (<0.1 s). Bleeding times were short, on the average less than 2 s, and did not differ between arterioles and venules. The duration of the embolization process was significantly longer in arterioles than in venules (median 101 and 17 s, respectively), and more emboli were produced in arterioles than in venules (median 6 and 1, respectively). Arteriolar thrombi were more effective in plugging the punctured holes than venular thrombi. The differences in thromboembolic reaction between arterioles and venules, as found in the present study, can probably not be explained by fluid dynamic factors.
Keywords: Vessel wall injury; Thrombus formation; Blood platelets; Intravital microscopy; Fluid dynamics